Evaluation of shale distribution in shaly-sand rocks on the basis of well logging data - the crossplots method - BAŁA, Maria (Geology, Geophysics and Environment, 2010)
The analysis of effects of shale distribution and clay volume in reservoir formations on well logging curves is presented in this paper. A conception given originally by Thomas & Stieber (1975) was applied into modelling the response of well logging tools for an assumed shaly-sand model. Results of calculations were compared with logs registered in the J4 well which drilled the autochthonous Miocene deposits. Different crossplots obtained based on Gamma Ray and Neutron and Density or Acoustic logs prove that there is a possibility to determine porosity, shale distribution and sand volume (net to gross) in the reservoir horizons.